Effect of plastic deformation at room temperature on hydrogen diffusion of S30408. (2nd April 2019) - Qu, Wenmin; Gu, Chaohua; Zheng, Jinyang; Zhao, Yongzhi; Hua, Zhengli
Abstract: Understanding the influence of plastic deformation on diffusion is critical for hydrogen embrittlement (HE) study. In this work, thermal desorption spectroscope (TDS), slow strain rate test (SSRT), feritscope, transmission electron microscope (TEM) and TDS model were used to study the relation between plastic deformation and hydrogen diffusion, aiming at unambiguously elucidating the effect of plastic deformation on hydrogen diffusion of austenitic stainless steel, S30408. An effective method was developed to deduce apparent hydrogen diffusion coefficient of austenitic stainless steel in this paper. Results indicate apparent hydrogen diffusion coefficient decreases firstly and then increases with increasing plastic deformation at room temperature. Hydrogen diffusion effected by plastic deformation is a complicated process which is suggested to be divided into two processes controlled by dislocation and strain-induced martensite, respectively, and the transition point is about 20% strain demonstrated by experiments in this case. Highlights: An effective method based on TDS was established to deduce apparent hydrogen diffusion coefficient of austenitic stainless steel. Quantitative relation between hydrogen diffusion coefficient and plastic deformation was established. The reason for the effect of plastic deformation on hydrogen diffusion was discussed from microstructures.